The Effect Of Breastfeeding Counseling On Breastfeeding Practices In Postpartum Mothers At RSIA Tiara Cikupa In 2022 - Rismayanti, Tetin; Muniroh, Muniroh (International Journal of Health and Pharmaceutical (IJHP), 2023)
According to the Health Profile of Banten Province in 2019, the number of babies who were exclusively breastfed was 56.1%, while the City of Tangerang itself was 64.5%. This figure is still below the government target that has been set for the success of breastfeeding by 80%. Research objectives is the effect of breastfeeding counseling on breastfeeding practices for postpartum mothers at RSIA Tiara Cikupa in 2022. Research method used preexperimental with one group pre test post test design. Sampling in this study used a total sampling technique and the sample size in the study was 30 postpartum mothers who had babies aged less than 6 months at RISA Tiara Cikupa. The research instrument used leaflets, teaching aids on how to breastfeed, and the LATCH questionnaire. Bivariate analysis used the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed that before being given counseling on how to breastfeed the respondents had an average value of breastfeeding practice of 2.63, while after being given counseling on how to breastfeed the respondents had an average value of breastfeeding practice of 6.57. There are differences in breastfeeding practices for postpartum mothers before and after being given breastfeeding counseling at RSIA Tiara Cikupa in 2022 with a p value of 0.001 0.05. It is hoped that they will further increase knowledge and skills about correct breastfeeding by following consultations with health workers, so that they can carry out correct breastfeeding practices effectively. independently and properly to improve the health status of mothers and babies.